Acupuncture Treatment of Guillain–Barré Syndrome After Using Immune Checkpoint Inhibitors: A Case Report - Li, Jialing; Xu, Danghan; Liu, Yingyu; Cao, Yang; He, Jun; Liao, Muxi (Frontiers in Neurology, 2022)
Guillain-Barré syndrome(GBS) is an autoimmune-mediated peripheral neuropathy. Immune checkpoint inhibitors(ICIs) are a standard treatment for cancer and may lead to immune-related adverse events (irAEs) such as GBS. Corticosteroids, plasma exchange (PE) and intravenous immunoglobulin (IVIG) are currently accepted treatments for ICIs-induced GBS. However, there are still adverse reactions, and the effect of relieving symptoms is not as good as expected. Safe and effective complementary replacement therapy to alleviate GBS symptoms and ameliorate the quality of life is urgently required. In this case, a 63-year-old man received ICIs therapy and anti-tumour chemotherapy for lung malignancy. After two courses of treatment, the patient gradually developed limb weakness, numbness and pain at the ends of the limbs, with cerebrospinal fluid (CSF) albuminocytological dissociation, electromyography (EMG) suggested demyelinating changes and was diagnosed as GBS. Although the patient received high doses of intravenous gamma globulin and limb weakness symptoms were alleviated, there was still significant numbness and pain in the extremities. After four times of acupuncture treatments, the patient complained that the symptoms of limb numbness and fatigue were significantly alleviated without any discomfort. This case report may provide a new alternative and complementary therapy for immune checkpoint inhibitor-induced GBS, but more definitive and robust evidence is needed to support its efficacy.